ChemInform Abstract: Ba2Cu2Te2P2O13: A New Telluro‐Phosphate with S=1/2 Heisenberg Chain. Issue 43 (October 2015) - Xia, Mingjun; Shen, Shipeng; Lu, Jun; Sun, Young; Li, R. K.
Abstract Single crystals of Ba2Cu2Te2P2O13 are grown by firing BaCO3, TeO2, CuO, and NH4H2PO4 in the molar ratio of 3:4:3:2, resp.